What are the general public’s expectations about the likely duration of common acute infections? A cross-sectional survey of Australian residents - Mark Jones; Tammy Hoffmann; Mina Bakhit; Kwame Peprah Boaitey (BMJ Open)
Objectives To explore the general public’s expectations about the likely duration of acute infections that are commonly managed in primary care and if care is sought for these infections, reasons for doing so.Design A cross-sectional online survey.Participants A nationwide sample of 589 Australian residents, ≥18 years old with representative quotas for age and gender, recruited via an online panel provider.Outcome measures For eight acute infections, participants’ estimated duration of each, time until they would seek care, and reasons for seeking care.Results For four infections, participants’ mean estimates of duration were within an evidence-based range—common cold (7.2 days), sore throat (5.2 days), acute otitis media (6.2 days) and impetigo (8.3 days); and >70% of the participants estimated a duration within the range. However, participants’ estimated mean duration was shorter than evidence-based estimates for acute cough (7.6 days), sinusitis (5.6 days), conjunctivitis (5.7 days) and uncomplicated urinary tract infections (UTIs; 5.4 days); and >60% of the participants underestimated the duration. Of the 589 participants, 365 (62%) indicated they were unlikely to routinely seek care for self-limiting infections. Most common reasons for care-seeking were severe or worsening symptoms, a desire for quick recovery and fear of progression to complications. After being shown typical durations, the proportion of participants who reported having no concerns waiting for spontaneous resolution while managing symptoms with over-the-counter medications ranged across the infections and was highest for common cold (68%) and lowest for UTI (31%).Conclusion Participants underestimated the duration of some infections compared with evidence-based estimates and were accurate in their estimates for other infections. Many stated that they would not be concerned about waiting for illnesses to self-resolve after learning the typical duration. Communicating the expected duration of common acute infections during routine consultations can help manage patients’ expectations of recovery and need to seek care.